Bilinear modelling and attitude control of a quadrotor - Seah, Chee Hwee; Inyang, Isonguyo J.; Whidborne, James F. (Elsevier, 2018)
The design of a bilinear controller for a quadrotor and its subsequent stability and performance are presented. A Carleman bilinearization technique is applied to the the nonlinear equations of motion of a quadrotor to obtain a bilinear model which is used as the basis for a bilinear PD controller design. For comparison purposes, a linear model of the quadrotor is also developed and used as the basis for PD controller design. Results for a transient simulation of the proposed BPD controller are presented and compared with that of the PD controller. The results show that the bilinear PD controller gives more improved responses over a broader operating range with respect to stability and performance compared to the PD controller.
Keywords: Quadrotor; Bilinear modelling; Attitude control; Bilinear PD